Improving Government Quality in the Regions of the EU and its System‐Wide Benefits for Cohesion Policy. (25th April 2022) - Barbero, Javier; Christensen, Martin; Conte, Andrea; Lecca, Patrizio; Rodríguez‐Pose, Andrés; Salotti, Simone
Abstract: We quantify the general equilibrium effects on economic growth of improving the quality of institutions at the regional level in the context of the implementation of the European Cohesion Policy for the European Union and the UK. The direct impact of changes in the quality of government is integrated in a general equilibrium model to analyse the system‐wide economic effects resulting from additional endogenous mechanisms and feedback effects. The results reveal a significant direct effect as well as considerable system‐wide benefits from improved government quality on economic growth. A small 5 per cent increase in government quality across European Union regions increases the impact of Cohesion investment by up to 7 per cent in the short run and 3 per cent in the long run. The exact magnitude of the gains depends on various local factors, including the initial endowments of public capital, the level of government quality, and the degree of persistence over time.